Global voices on atrial fibrillation care in China - Li, Mingfang; Chen, Minglong; Guo, Yutao; Lip, Gregory Y.H. (Heart rhythm O2, 2024)
An aging population, coupled with the high prevalence of physical inactivity, obesity, dyslipidemia, hypertension, and diabetes mellitus, has led to a significant increase in the incidence and prevalence of atrial fibrillation (AF) in China. Managing clinical complexity of AF patients poses significant challenges. Current guidelines advocate for holistic or integrated management using the ABC (Atrial fibrillation Better Care) pathway. Compliance with the ABC pathway has demonstrated promising benefit in improving clinical outcomes. The mAFA II trial (the mHealth technology for improved screening, patient involvement, and optimized integrated care in Atrial Fibrillation) explores the potential of a mobile health technology–supported integrated care approach in reducing the risks of rehospitalization and clinical adverse events. However, disparities persist between urban and rural areas, with the likelihood of rural older individuals by themselves using intelligent devices being extremely low. Therefore, the application prospects of the mobile AF application strategy in rural areas are greatly limited. The ongoing MIRACLE-AF trial (A Novel Model of Integrated Care of Older Patients With Atrial Fibrillation in Rural China) aims to address unique healthcare challenges faced by rural older patients with AF through a novel integrated care model, which is led by village doctors and supported by a digital health platform. In conclusion, innovative integrated care approaches using digital technologies offer promising solutions to enhance AF care across diverse settings in China, catering to the needs of both urban and rural populations.